Male Alternative Reproductive Tactics and Associated Evolution of Anatomical Characteristics in Loliginid Squid - Marian, José E. A. R.; Apostólico, Lígia H.; Chiao, Chuan-Chin; Hanlon, Roger T.; Hirohashi, Noritaka; Iwata, Yoko; Mather, Jennifer; Sato, Noriyosi; Shaw, Paul W. (Frontiers in Physiology, 2019)
Loliginid squids provide a unique model system to explore male alternative reproductive tactics (ARTs) and their linkage to size, behavioral decision making, and possibly age. Large individuals fight one another and the winners form temporary consortships with females, while smaller individuals do not engage in male-male agonistic bouts but use various sneaker tactics to obtain matings, each with varying mating and fertilization success. There is substantial behavioral flexibility in most species, as smaller males can facultatively switch to the alternative consort behaviors as the behavioral context changes. These forms of ARTs involve different: mating posture; site of spermatophore deposition; fertilization success; and sperm traits. Most of the traits of male dimorphism (both anatomical and behavioral) are consistent with traditional sexual selection theory, while others have unique features that may have evolved in response to the fertilization environment faced by each temporary or permanent male morph.